Longitudinal changes of oxidative stress and PON1 lactonase activity and status in older pregnant women undergoing assisted reproductive technology: a prospective nested case-control study - Chenyu Jiang; Meng Chen; Yujie Wu; Huai Bai; Xinghui Liu; Ping Fan (BMC, 2023)
Abstract Background Childbearing in women with advanced maternal age (AMA) has increased the need for artificial reproductive technology (ART). ART and oxidative stress are associated with many pregnancy complications. Paraoxonase (PON) 1 is one of the key components responsible for antioxidative activity in high-density lipoprotein (HDL). This study aimed to investigate the longitudinal changes of oxidative stress and PON1 lactonase activity and status in older women undergoing ART. Methods This prospective nested case-control study included 129 control and 64 ART women. Blood samples were obtained respectively at different stages of pregnancy. PON1 level and lactonase activity were assessed using 7-O-diethylphosphoryl-3-cyano-4-methyl-7-hydroxycoumarin (DEPCyMC) and 5-thiobutyl butyrolactone (TBBL) as a substrate, respectively. A normalized lactonase activity (NLA) was estimated based on the ratio of TBBLase to DEPCyMCase activity. Serum total oxidant status (TOS), total antioxidant capacity (TAC), malondialdehyde (MDA), homocysteine (HCY), PON1 C-108T and Q192R genetic polymorphisms, and metabolic parameters were analyzed. Results Lactonase activity and level of PON1 gradually decreased with pregnancy progression, while glycolipid metabolism parameters and TAC levels increased with pregnancy progression or significantly raised during the 2nd and 3rd trimesters, and NLA of PON1, TOS, OSI, MDA, and HCY significantly increased before delivery in the ART and control groups. Compared with the control women, the ART women had substantially higher or relatively high lactonase activity and NLA of PON1 and TAC during pregnancy; higher triglyceride (TG), total cholesterol, low-density lipoprotein cholesterol, atherogenic index, apolipoprotein (apo) B, and apoB/apoA1 ratio in the 1st trimester; and higher fasting glucose, fasting insulin, homeostatic model assessment of insulin resistance, and TG levels before delivery. No significant differences were found in the frequencies of PON1 C-108T and Q192R genotypes and alleles between the ART and control groups. Conclusions Women with AMA undergoing ART had higher TAC, PON1 lactonase activity, and PON1 NLA than control women, suggesting increased compensatory antioxidant capacity in ART women, thus showing higher sensitivity to oxidative stress-related injury and diseases.